A composite hollow fiber nanofiltration membrane and its preparation method and application
The composite hollow fiber nanofiltration membrane was prepared by dopamine-encapsulated Ni-MOF/PDA material and layer-by-layer self-assembly method, which solved the problems of low flux and low salt retention in the existing nanofiltration membrane, and achieved efficient water treatment and biomedical applications.
Patent Information
- Application Number
- CN202411963185.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing nanofiltration membrane preparation methods are complex, have low flux and low salt retention, which are difficult to meet the needs of efficient separation in the fields of water treatment and biomedical.
The composite hollow fiber nanofiltration membrane was prepared by dopamine-encapsulated Ni-MOF/PDA metal organic framework material, and the polycationic electrolyte and polyanionic electrolyte were alternately coated on the hollow fiber ultrafiltration membrane by layer-by-layer self-assembly method.
The hydrophilicity and positive charge density of the nanofiltration membrane are improved, the retention rate of divalent cations is significantly enhanced, and high throughput and high salt retention is achieved, suitable for water treatment and biomedical fields.
Smart Images

Figure CN119746640A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanofiltration membranes, and in particular to a composite hollow fiber nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] Nanofiltration membranes play a vital role in water treatment, separation technology and environmental protection, especially in removing tiny pollutants, heavy metal ions and organic matter. Nanofiltration membrane technology can effectively intercept particles with a diameter of 1 to 10 nm. This feature enables it to remove fine suspended matter, viruses and bacteria in water while allowing water molecules and some beneficial minerals such as calcium and magnesium to pass through, thereby ensuring the safety and nutrition of water quality. The efficient separation ability of nanofiltration membranes can not only significantly improve water quality and reduce the concentration of harmful substances, but also retain elements that are beneficial to human health. Therefore, it is particularly important in drinking water purification, especially in ensuring the sustainable development of public health and the ecological environment.
[0003] At present, commercial nanofiltration membrane materials are mainly based on traditional interfacial polymerization technology, and their permeation separation performance mainly depends on the characteristics of the polyamide separation layer. Although polyamide nanofiltration membranes are widely used in the field of water treatment, they still have some limitations. First, polyamide membranes have poor tolerance to certain solvents and chemicals and are prone to swelling or degradation. This phenomenon is particularly obvious in high temperature or strong acid and alkali environments, which limits their application under extreme environmental conditions. Secondly, polyamide nanofiltration membranes face the problem of fouling. The accumulation of dirt and microorganisms will significantly reduce the flux and separation efficiency of the membrane, forcing operators to clean and maintain it regularly to ensure its normal operation. Thirdly, the production cost of polyamide nanofiltration membranes is high, and the problem of insufficient mechanical strength may occur during long-term use. These factors pose challenges to their widespread application in certain specific application scenarios. Therefore, the development of new materials, improvement of membrane structure and optimization of production processes to overcome these limitations remain the hot spots and directions of current research.
[0004] Patent CN118437168A discloses a method for preparing an in-situ antibacterial polyamide nanofiltration membrane containing an imidazole structure. First, the casting liquid is used to prepare a base membrane by a phase inversion method, and then a bis-imidazoline aqueous monomer containing an imidazole structure and an amino terminal structure is obtained by amidation and cyclization. Finally, an interfacial polymerization reaction is performed to form an in-situ antibacterial polyamide nanofiltration membrane containing an imidazole structure. Under an operating pressure of 8 bar, the membrane has a magnesium sulfate rejection rate of 71-95%, and the preparation process uses an organic solvent, and the process steps are relatively complicated. Patent CN115155341A discloses an antibacterial composite nanofiltration membrane and a preparation method thereof. The composite nanofiltration membrane uses a polysulfone ultrafiltration membrane as a base membrane. On the surface of the base membrane, an ultrathin polyamide layer is formed by interfacial polymerization using piperazine and trimesoyl chloride solution. Subsequently, the composite nanofiltration membrane is immersed in a photoreduction solution and irradiated under ultraviolet light. The water flux is 7 to 12 L / (m·h·bar). However, the preparation process uses precious metals and a variety of instruments to assist in the preparation of the nanofiltration membrane, which is relatively costly.
[0005] Therefore, it is of great significance to study a method for preparing a composite hollow fiber nanofiltration membrane with simple preparation method, low cost, high flux and salt retention rate, and the application of the obtained composite hollow fiber nanofiltration membrane in pollution control or biomedical fields. Summary of the invention
[0006] In view of this, the present invention provides a composite hollow fiber nanofiltration membrane and a preparation method and application thereof, the purpose of which is to solve the problems of complex preparation method, low flux and low salt retention rate in the prior art.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention provides a method for preparing a composite hollow fiber nanofiltration membrane, comprising the following steps:
[0009] 1) mixing 1,4-diphenyl(4-pyrazolyl)benzene, nickel acetate and a first solvent and drying the mixture to obtain Ni-MOF;
[0010] 2) mixing Ni-MOF, dopamine hydrochloride and a second solvent and then coating with PDA to obtain Ni-MOF / PDA;
[0011] 3) mixing Ni-MOF / PDA with a polycation electrolyte to obtain a polycation electrolyte containing Ni-MOF / PDA;
[0012] 4) A layer-by-layer self-assembly method is used to alternately coat a polycation electrolyte solution and a polyanion electrolyte solution containing Ni-MOF / PDA on a hollow fiber ultrafiltration membrane to obtain a composite hollow fiber nanofiltration membrane.
[0013] Preferably, in step 1), the first solvent is tetrahydrofuran and / or chloroform;
[0014] The usage ratio of the 1,4-diphenyl(4-pyrazolyl)benzene, nickel acetate and the first solvent is 1 mol: 0.5-5 mol: 180-220 mL.
[0015] Preferably, in step 1), the mixing time is 30 to 50 minutes;
[0016] The drying time is 8 to 12 hours, and the drying temperature is 120 to 150°C.
[0017] Preferably, in step 2), the second solvent is n-hexane;
[0018] The usage ratio of the Ni-MOF, dopamine hydrochloride and the second solvent is 0.3-1 mol: 90-150 mg: 80-120 mL.
[0019] Preferably, in step 2), the PDA encapsulation step is: after mixing Ni-MOF, dopamine hydrochloride and the second solvent, removing the supernatant, adding ethanol, water and ammonia water to the obtained product and stirring, and then centrifuging to complete the PDA encapsulation;
[0020] The mixing time is 80 to 120 minutes, the dosage ratio of Ni-MOF, ethanol, water and ammonia water is 0.3 to 1 mol: 150 to 300 mL: 250 to 350 mL: 1 to 3 mL, the stirring time is 80 to 120 minutes, the centrifugal speed is 7000 to 10000 rpm, and the centrifugal time is 2 to 5 minutes.
[0021] Preferably, in step 3), the polycation electrolyte is polyacrylamine hydrochloride or polystyreneamine;
[0022] The molar ratio of Ni-MOF / PDA to polycation electrolyte is 5-50:50-95.
[0023] Preferably, in step 3), the mixing time is 10 to 60 minutes and the mixing temperature is 15 to 25°C.
[0024] Preferably, in step 4), the polyanion electrolyte is polystyrene sulfonic acid, polyacrylic acid, dextran sulfate or sodium polyvinyl sulfonate;
[0025] The solvent of the polycation electrolyte solution containing Ni-MOF / PDA and the solvent of the polyanion electrolyte solution are independently sodium chloride solutions, and the concentration of the sodium chloride solution is 0.5-2.5M; the number of layers of the coating obtained by coating is 5-8 layers.
[0026] The present invention also provides a composite hollow fiber nanofiltration membrane prepared by the method for preparing the composite hollow fiber nanofiltration membrane.
[0027] The invention also provides application of the composite hollow fiber nanofiltration membrane in sewage treatment or biomedical fields.
[0028] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0029] The dopamine encapsulation method of the present invention can introduce amino groups without destroying the Ni-MOF structure, thereby enhancing the hydrophilicity of the metal organic framework Ni-MOF / PDA, thereby enhancing the hydrophilicity of the nanofiltration membrane. At the same time, the amino structure of Ni-MOF / PDA can increase the positive charge density of the polycation electrolyte and the nanofiltration membrane, so the nanofiltration membrane of the present invention can improve the retention rate of divalent cations. Moreover, the present invention adopts a layer-by-layer self-assembly method to prepare the nanofiltration membrane, and the amino-containing polycation electrolyte and the polyanion electrolyte with opposite charge are assembled under the action of entropy increase to obtain a high-flux composite hollow fiber nanofiltration membrane. Therefore, the hollow fiber nanofiltration membrane of the present invention has good hydrophilicity, and the water contact angle is reduced to 25°, which is a hydrophilic membrane; and it has a higher pure water flux, and the water flux of the nanofiltration membrane is 50L / (m 2 h) or above.
[0030] The Ni-MOF / PDA metal organic framework material added to the polycation electrolyte used in the present invention contains positively charged amino groups, which can increase the positive charge density of the nanofiltration membrane, so that the nanofiltration membrane has a retention rate of magnesium sulfate of more than 96%.
[0031] The layer-by-layer self-assembly method adopted by the present invention is based on water solvent, and the preparation process is green and environmentally friendly, and the cost is low, and it is easier to industrialize production.
[0032] The hollow fiber nanofiltration membrane prepared by the present invention can also be adjusted according to specific application requirements in the field of water treatment (such as drinking water treatment, seawater desalination, soil and water pollution control, etc.) or biomedical field to meet the use requirements under different industrial and environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0034] Figure 1 Schematic diagram of the structure of Ni-MOF and Ni-MOF / PDA in the present invention;
[0035] Figure 2 FTIR images of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1;
[0036] Figure 3 is the XRD pattern of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1;
[0037] Figure 4 is the adsorption / desorption diagram of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1;
[0038] Figure 5 The SEM images of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1;
[0039] Figure 6 TEM images of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1;
[0040] Figure 7 Graphs showing contact angles of the composite hollow fiber nanofiltration membranes obtained in Comparative Example 1 and Examples 1 to 3;
[0041] Figure 8 It is a water permeability diagram of the composite hollow fiber nanofiltration membrane obtained in Comparative Example 1 and Examples 1 to 3;
[0042] Fig. 9 Graph showing the salt rejection of the composite hollow fiber nanofiltration membranes obtained in Comparative Example 1 and Examples 1 to 3. DETAILED DESCRIPTION
[0043] The present invention provides a method for preparing a composite hollow fiber nanofiltration membrane, comprising the following steps:
[0044] 1) mixing 1,4-diphenyl(4-pyrazolyl)benzene, nickel acetate and a first solvent and drying the mixture to obtain Ni-MOF;
[0045] 2) mixing Ni-MOF, dopamine hydrochloride and a second solvent and then coating with PDA to obtain Ni-MOF / PDA;
[0046] 3) mixing Ni-MOF / PDA with a polycation electrolyte to obtain a polycation electrolyte containing Ni-MOF / PDA;
[0047] 4) A layer-by-layer self-assembly method is used to alternately coat a polycation electrolyte solution and a polyanion electrolyte solution containing Ni-MOF / PDA on a hollow fiber ultrafiltration membrane to obtain a composite hollow fiber nanofiltration membrane.
[0048] In the present invention, in step 1), the first solvent is preferably tetrahydrofuran and / or chloroform;
[0049] The usage ratio of the 1,4-diphenyl(4-pyrazolyl)benzene, nickel acetate and the first solvent is preferably 1 mol:0.5-5 mol:180-220 mL, more preferably 1 mol:1.5-4.5 mol:190-210 mL, and more preferably 1 mol:2-3 mol:200-205 mL.
[0050] In the present invention, in the step 1), the mixing is preferably ultrasonic mixing, and the ultrasonic mixing time is preferably 30 to 50 minutes, more preferably 35 to 45 minutes, and more preferably 38 to 40 minutes;
[0051] The drying time is preferably 8 to 12 hours, more preferably 9 to 11 hours, and more preferably 9.5 to 10 hours. The drying temperature is preferably 120 to 150°C, more preferably 125 to 145°C, and more preferably 130 to 140°C.
[0052] In the present invention, in the step 1), washing and centrifugation are sequentially performed after mixing, the washing reagent is preferably ethanol, the number of washings is preferably 3 to 6 times, more preferably 4 to 5 times, the centrifugal speed is preferably 1400 to 1700 rpm, more preferably 1500 to 1600 rpm, and the centrifugal time is preferably 2 to 6 min, more preferably 3 to 5 min, and more preferably 4 min.
[0053] In the present invention, in the step 2), the second solvent is preferably n-hexane;
[0054] The usage ratio of the Ni-MOF, dopamine hydrochloride and the second solvent is preferably 0.3-1 mol:90-150 mg:80-120 mL, more preferably 0.4-0.8 mol:100-140 mg:95-115 mL, and more preferably 0.5-0.6 mol:110-120 mg:100-110 mL.
[0055] In the present invention, in the step 2), the PDA encapsulation step is: after mixing Ni-MOF, dopamine hydrochloride and the second solvent, removing the supernatant, adding ethanol, water and ammonia water to the obtained product and stirring, and then centrifuging to complete the PDA encapsulation;
[0056] The mixing time is preferably 80 to 120 min, more preferably 90 to 115 min, and more preferably 100 to 110 min. The dosage ratio of Ni-MOF, ethanol, water and aqueous ammonia is preferably 0.3 to 1 mol: 150 to 300 mL: 250 to 350 mL: 1 to 3 mL, more preferably 0.4 to 0.8 mol: 170 to 280 mL: 260 to 330 mL: 1.5 to 2.5 mL, and more preferably 0.5 to 0.6 mol: 200 to 250 mL: 280 to 330 mL: 300mL:1.75~2mL, the concentration of the ammonia water is preferably 25~28wt%, more preferably 26~27wt%, the stirring time is preferably 80~120min, more preferably 85~110min, more preferably 90~100min, the centrifugal speed is preferably 7000~10000rpm, more preferably 8000~9500rpm, more preferably 8500~9000rpm, the centrifugal time is preferably 2~5min, more preferably 3~4min.
[0057] In the present invention, in step 3), the polycation electrolyte is preferably polyacrylamine hydrochloride or polystyreneamine;
[0058] The molar ratio of Ni-MOF / PDA to the polycation electrolyte is preferably 5-50:50-95, more preferably 15-40:60-85, and even more preferably 20-30:70-80.
[0059] In the present invention, in step 3), the mixing time is preferably 10 to 60 min, more preferably 20 to 50 min, more preferably 30 to 40 min, and the mixing temperature is preferably 15 to 25°C, more preferably 17 to 23°C, more preferably 18 to 20°C.
[0060] In the present invention, in step 4), the polyanion electrolyte is preferably polystyrene sulfonic acid, polyacrylic acid, dextran sulfate or sodium polyvinyl sulfonate;
[0061] The concentration of the polycation electrolyte solution containing Ni-MOF / PDA is preferably 8 to 12 g / L, more preferably 9 to 11 g / L, and more preferably 10 g / L;
[0062] The concentration of the polyanion electrolyte solution is preferably 2 to 6 g / L, more preferably 3 to 5 g / L, and more preferably 4 g / L;
[0063] The solvent of the polycationic electrolyte solution containing Ni-MOF / PDA and the solvent of the polyanionic electrolyte solution are independently preferably sodium chloride solutions, and the concentration of the sodium chloride solution is preferably 0.5 to 2.5 M, more preferably 0.8 to 2.2 M, and more preferably 1.2 to 1.5 M; the number of layers of the coating obtained by coating is preferably 5 to 8 layers, and more preferably 6 to 7 layers.
[0064] In the present invention, in step 4), the steps of the layer-by-layer self-assembly method are:
[0065] a. injecting the polyanion electrolyte solution into the inner cavity of the hollow fiber ultrafiltration membrane through a peristaltic pump, and obtaining the first layer of coating after standing, and then cleaning the inner cavity of the hollow fiber ultrafiltration membrane;
[0066] b. The polycation electrolyte solution containing Ni-MOF / PDA is pumped into the inner cavity of the hollow fiber ultrafiltration membrane coated with the first layer of coating by a peristaltic pump, and the second layer of coating is obtained after standing, and then the inner cavity of the hollow fiber ultrafiltration membrane is cleaned;
[0067] c. Alternately repeating steps a and b to obtain a composite hollow fiber nanofiltration membrane;
[0068] The cleaning is preferably performed by flushing with deionized water until the conductivity of the eluate is close to that of water, and then the excess liquid in the cavity of the hollow fiber ultrafiltration membrane is blown dry with compressed air; the time for each flushing is preferably 3 to 6 minutes, and more preferably 4 to 5 minutes;
[0069] The temperatures of the polyanion electrolyte solution and the polycation electrolyte solution containing Ni-MOF / PDA are independently preferably 18 to 25°C, more preferably 20 to 24°C, and even more preferably 21 to 23°C.
[0070] The present invention also provides a composite hollow fiber nanofiltration membrane prepared by the method for preparing the composite hollow fiber nanofiltration membrane.
[0071] The invention also provides application of the composite hollow fiber nanofiltration membrane in sewage treatment or biomedical fields.
[0072] In the present invention, the sewage treatment is preferably drinking water treatment, seawater desalination, soil and water pollution control.
[0073] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0074] In the embodiment of the present invention, a polyethersulfone hollow fiber ultrafiltration membrane is used as the hollow fiber membrane.
[0075] Example 1
[0076] 1.0 mol of 1,4-diphenyl(4-pyrazolyl)benzene and 1.0 mol of nickel acetate were ultrasonically mixed with 200 mL of tetrahydrofuran in a three-necked flask for 40 min, then washed with anhydrous ethanol for 4 times, and then centrifuged at 1500 rpm for 3 min to obtain a precipitate, and the obtained precipitate was dried at 130°C for 10 h to obtain Ni-MOF;
[0077] 0.3 mol Ni-MOF, 100 mL anhydrous n-hexane and 120 mg dopamine hydrochloride were mixed and stirred for 100 min, and then the supernatant was removed. 200 mL anhydrous ethanol, 300 mL deionized water and 2 mL ammonia water (concentration of 25 wt%) were added to the obtained product, and after stirring for 100 min, the mixture was centrifuged at 8000 rpm for 4 min to obtain Ni-MOF / PDA.
[0078] 0.1 mol Ni-MOF / PDA and 0.9 mol polyacrylamine hydrochloride powder were mixed at 20°C for 30 min to obtain a polycationic electrolyte containing Ni-MOF / PDA, which was recorded as "polycationic electrolyte of Ni-MOF / PDA (10)";
[0079] A 4 g / L polystyrene sulfonic acid solution (solvent is 0.5 M NaCl aqueous solution) at 21°C was injected into the inner cavity of the hollow fiber membrane through a peristaltic pump and allowed to stand for 5 minutes to form a first layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0080] A polycation electrolyte solution (solvent: 2.5 M NaCl aqueous solution) containing Ni-MOF / PDA (10) at a concentration of 10 g / L at 21°C was injected into the inner cavity of the hollow fiber membrane coated with the first layer of coating through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0081] The above coating steps were repeated alternately to obtain a composite hollow fiber nanofiltration membrane having 6 layers of coating and containing Ni-MOF / PDA (10) polyelectrolyte.
[0082] Example 2
[0083] 1.0 mol of 1,4-diphenyl(4-pyrazolyl)benzene and 1.0 mol of nickel acetate were ultrasonically mixed with 200 mL of tetrahydrofuran in a three-necked flask for 40 min, then washed with anhydrous ethanol for 4 times, and then centrifuged at 1500 rpm for 3 min to obtain a precipitate, and the obtained precipitate was dried at 130°C for 10 h to obtain Ni-MOF;
[0084] 0.3 mol Ni-MOF, 100 mL anhydrous n-hexane and 120 mg dopamine hydrochloride were mixed and stirred for 100 min, and then the supernatant was removed. 200 mL anhydrous ethanol, 300 mL deionized water and 2 mL ammonia water (concentration of 25 wt%) were added to the obtained product, and after stirring for 100 min, the mixture was centrifuged at 8000 rpm for 4 min to obtain Ni-MOF / PDA.
[0085] 0.25 mol Ni-MOF / PDA and 0.75 mol polyacrylamine hydrochloride powder were mixed at 20°C for 30 min to obtain a polycationic electrolyte containing Ni-MOF / PDA, which was recorded as "polycationic electrolyte containing Ni-MOF / PDA (25)";
[0086] A 4 g / L polystyrene sulfonic acid solution (solvent is 0.5 M NaCl aqueous solution) at 21°C was injected into the inner cavity of the hollow fiber membrane through a peristaltic pump and allowed to stand for 5 minutes to form a first layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0087] A polycation electrolyte solution (solvent: 2.5 M NaCl aqueous solution) containing Ni-MOF / PDA (25) at a concentration of 10 g / L at 21°C was injected into the inner cavity of the hollow fiber membrane coated with the first layer of coating through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0088] The above coating steps were repeated alternately to obtain a composite hollow fiber nanofiltration membrane with 6 layers of coating containing Ni-MOF / PDA (25) polyelectrolyte.
[0089] Example 3
[0090] 1.0 mol of 1,4-diphenyl(4-pyrazolyl)benzene and 1.0 mol of nickel acetate were ultrasonically mixed with 200 mL of tetrahydrofuran in a three-necked flask for 40 min, then washed with anhydrous ethanol 4 times, and then centrifuged at 1500 rpm for 4 min to obtain a precipitate, and the obtained precipitate was dried at 130°C for 10 h to obtain Ni-MOF;
[0091] 0.3 mol Ni-MOF, 100 mL anhydrous n-hexane and 120 mg dopamine hydrochloride were mixed and stirred for 100 min, and then the supernatant was removed. 200 mL anhydrous ethanol, 300 mL deionized water and 2 mL ammonia water (concentration of 26 wt%) were added to the obtained product, and after stirring for 100 min, the mixture was centrifuged at 8000 rpm for 4 min to obtain Ni-MOF / PDA.
[0092] 0.5 mol of Ni-MOF / PDA and 0.5 mol of polyacrylamine hydrochloride powder were mixed at 20°C for 30 min to obtain a polycationic electrolyte containing Ni-MOF / PDA, which was recorded as "polycationic electrolyte containing Ni-MOF / PDA (50)";
[0093] A 4 g / L polystyrene sulfonic acid solution (solvent is 0.5 M NaCl aqueous solution) at 21°C was injected into the inner cavity of the hollow fiber membrane through a peristaltic pump and allowed to stand for 5 minutes to form a first layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0094] A polycation electrolyte solution (solvent: 2.5 M NaCl aqueous solution) containing Ni-MOF / PDA (50) at a concentration of 10 g / L at 21°C was injected into the inner cavity of the hollow fiber membrane coated with the first layer of coating through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0095] The above coating steps were repeated alternately to obtain a composite hollow fiber nanofiltration membrane having 6 layers of coating and containing Ni-MOF / PDA (50) polyelectrolyte.
[0096] Example 4
[0097] 1.0 mol of 1,4-diphenyl(4-pyrazolyl)benzene and 1.0 mol of nickel acetate were ultrasonically mixed with 200 mL of tetrahydrofuran in a three-necked flask for 40 min, then washed with anhydrous ethanol for 4 times, and then centrifuged at 1500 rpm for 5 min to obtain a precipitate, and the obtained precipitate was dried at 130°C for 10 h to obtain Ni-MOF;
[0098] 0.3 mol Ni-MOF, 100 mL anhydrous n-hexane and 120 mg dopamine hydrochloride were mixed and stirred for 100 min, and then the supernatant was removed. 200 mL anhydrous ethanol, 300 mL deionized water and 2 mL ammonia water (concentration of 26 wt%) were added to the obtained product, and after stirring for 100 min, the mixture was centrifuged at 8000 rpm for 4 min to obtain Ni-MOF / PDA.
[0099] 0.5 mol of Ni-MOF / PDA and 0.5 mol of polystyrene amine powder were mixed at 20°C for 30 min to obtain a polycationic electrolyte containing Ni-MOF / PDA, which was recorded as "polycationic electrolyte containing Ni-MOF / PDA (50)";
[0100] A 4 g / L polyacrylic acid solution (solvent is 0.5 M NaCl aqueous solution) at 20°C was injected into the inner cavity of the hollow fiber membrane through a peristaltic pump and allowed to stand for 5 minutes to form a first layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water. After that, the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air.
[0101] A polycation electrolyte solution (solvent: 2.5 M NaCl aqueous solution) containing Ni-MOF / PDA (50) at a concentration of 10 g / L at 20°C was injected into the inner cavity of the hollow fiber membrane coated with the first layer of coating through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0102] The above coating steps were repeated alternately to obtain a composite hollow fiber nanofiltration membrane having 6 layers of coating and containing Ni-MOF / PDA (50) polyelectrolyte.
[0103] Example 5
[0104] 1.0 mol of 1,4-diphenyl(4-pyrazolyl)benzene and 1.0 mol of nickel acetate were ultrasonically mixed with 200 mL of tetrahydrofuran in a three-necked flask for 40 min, then washed with anhydrous ethanol 4 times, and then centrifuged at 1500 rpm for 4 min to obtain a precipitate, and the obtained precipitate was dried at 130°C for 10 h to obtain Ni-MOF;
[0105] 0.3 mol Ni-MOF, 100 mL anhydrous n-hexane and 120 mg dopamine hydrochloride were mixed and stirred for 100 min, and then the supernatant was removed. 200 mL anhydrous ethanol, 300 mL deionized water and 2 mL ammonia water (concentration of 25 wt%) were added to the obtained product, and after stirring for 100 min, the mixture was centrifuged at 8000 rpm for 4 min to obtain Ni-MOF / PDA.
[0106] 0.5 mol of Ni-MOF / PDA and 0.5 mol of polystyrene amine powder were mixed at 20°C for 30 min to obtain a polycationic electrolyte containing Ni-MOF / PDA, which was recorded as "polycationic electrolyte containing Ni-MOF / PDA (50)";
[0107] A polycation electrolyte solution (solvent: 2.5 M NaCl aqueous solution) containing Ni-MOF / PDA (50) at a concentration of 10 g / L at 22°C was injected into the inner cavity of the hollow fiber membrane through a peristaltic pump and allowed to stand for 5 min to form a first layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 min until the conductivity of the effluent was close to that of deionized water. After that, the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air.
[0108] A 4 g / L polyacrylic acid solution (solvent is 0.5 M NaCl aqueous solution) at 22°C is injected into the inner cavity of the hollow fiber membrane through a peristaltic pump, and allowed to stand for 5 minutes to form a second coating layer. The inner cavity coated with the first coating layer is flushed with deionized water for 4 minutes until the conductivity of the effluent is close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane is blown dry with compressed air;
[0109] The above coating steps were repeated alternately to obtain a composite hollow fiber nanofiltration membrane having 6 layers of coating and containing Ni-MOF / PDA (50) polyelectrolyte.
[0110] Comparative Example 1
[0111] 1.0 mol of 1,4-diphenyl(4-pyrazolyl)benzene and 1.0 mol of nickel acetate were ultrasonically mixed with 200 mL of tetrahydrofuran in a three-necked flask for 40 min, then washed with anhydrous ethanol for 4 times, and then centrifuged at 1500 rpm for 3 min to obtain a precipitate, and the obtained precipitate was dried at 130°C for 10 h to obtain Ni-MOF;
[0112] 0.1 mol Ni-MOF and 0.9 mol polyacrylamine hydrochloride powder were mixed at 20°C for 30 min to obtain a polycationic electrolyte containing Ni-MOF, which was recorded as "polycationic electrolyte of Ni-MOF (0)";
[0113] A 4 g / L polystyrene sulfonic acid solution (solvent is 0.5 M NaCl aqueous solution) at 21°C was injected into the inner cavity of the hollow fiber membrane through a peristaltic pump and allowed to stand for 5 minutes to form a first layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0114] A polycation electrolyte solution (solvent: 2.5 M NaCl aqueous solution) containing Ni-MOF(0) at a concentration of 10 g / L at 21°C was injected into the inner cavity of the hollow fiber membrane coated with the first layer of coating through a peristaltic pump, and allowed to stand for 5 minutes to form a second layer of coating. The inner cavity of the hollow fiber membrane was flushed with deionized water for 4 minutes until the conductivity of the effluent was close to that of deionized water, and then the excess liquid in the inner cavity of the hollow fiber membrane was blown dry with compressed air;
[0115] The above coating steps were repeated alternately to obtain a composite hollow fiber nanofiltration membrane having 6 layers of coating and containing Ni-MOF (0) polyelectrolyte.
[0116] The hollow fiber nanofiltration membranes obtained in Example 1 and Comparative Example 1 were tested for performance:
[0117] Permeability test:
[0118] The permeability of the composite hollow fiber nanofiltration membranes obtained in Examples 1 to 3 and Comparative Example 1 was tested respectively, and the test steps were as follows:
[0119] The cross-flow method was adopted, and the cross-flow velocity was 0.65 m / s at 3 bar, using an experimental scale cross-flow filtration device for determination. The water permeability was tested. The water permeability was calculated using formula (I):
[0120]
[0121] In formula I, P(L / m 2 ·h·bar) is the permeability, ΔV(L) is the permeation volume, A(m 2 ) is the effective area of the membrane, Δt (h) is the permeate collection time, and Δp (bar) is the average transmembrane pressure at the inlet and outlet of the membrane module in Formula I.
[0122] The permeability graph of the composite hollow fiber nanofiltration membrane obtained in Comparative Example 1 and Examples 1 to 3 of the present invention is as follows: Figure 8 As shown. Figure 8 It can be seen that under the test condition of 3 bar, the permeability of the nanofiltration membrane obtained in Comparative Example 1 with only Ni-MOF without dopamine coating to MgCl2, MgSO4, Na2SO4, and NaCl with a concentration of 500 mg / L is 43 L / (m -2 ·h·bar); after adding Ni-MOF / PDA (10), the metal organic framework was introduced into the separation layer of the nanofiltration membrane, thereby enhancing the hydrophilicity of the nanofiltration membrane, thereby increasing the permeability of the composite hollow fiber nanofiltration membrane obtained in Example 1 to 51L / (m -2 ·h·bar); after adding Ni-MOF / PDA(25), hydrophilic dopamine was introduced into the separation layer of the nanofiltration membrane, thereby enhancing the hydrophilicity of the nanofiltration membrane, and the permeability of the composite hollow fiber nanofiltration membrane obtained in Example 2 increased to 53L / (m -2 ·h·bar); after adding Ni-MOF / PDA(50), hydrophilic dopamine was introduced into the separation layer of the nanofiltration membrane, thereby increasing the permeability of the composite hollow fiber nanofiltration membrane obtained in Example 3 to 55L / (m -2 ·h·bar).
[0123] Salt retention test:
[0124] The composite hollow fiber nanofiltration membranes obtained in Examples 1 to 5 and Comparative Example 1 were respectively subjected to the following tests to measure the salt retention rate. The test steps are as follows:
[0125] 500 mg / L MgCl2, 500 mg / L MgSO4, 500 mg / L Na2SO4, and 500 mg / L NaCl solutions were respectively delivered to the inner cavity of the composite hollow fiber nanofiltration membrane by a gear pump. After stable cross-flow operation at a flow rate of 0.65 m / s at a pressure of 3 bar for 1 hour, a sample from the permeate side was taken to measure the concentration of the permeate, which was measured by a conductivity meter (FE30, Mettler Toledo). The retention rate was calculated using formula (II):
[0126]
[0127] In formula (Ⅱ), R is the interception rate, C p is the permeate concentration, C f is the feed solution concentration.
[0128] The test results are shown in Table 1 and Fig. 9 As shown:
[0129] Table 1 Salt retention test results of the composite hollow fiber nanofiltration membrane obtained in Examples 1 to 5 and Comparative Example 1
[0130]
[0131] The salt retention rate of the composite hollow fiber nanofiltration membrane obtained in Comparative Example 1 and Examples 1 to 3 of the present invention is shown in FIG. Fig. 9 Combining Table 1 and Fig. 9 It can be seen that under the test condition of 3 bar, the nanofiltration membrane in comparative example 1, to which only non-dopamined Ni-MOF was added, had a retention capacity of MgSO4>MgCl2>NaCl>Na2SO4 for metal salts with a concentration of 500 mg / L. The polyelectrolyte composite hollow fiber nanofiltration membrane containing Ni-MOF(0) had retention rates of 82% and 85% for MgCl2 and MgSO4, respectively, while the retention rate for Na2SO4 was relatively low, at 48%. In the present invention, dopamine with adhesiveness was introduced into the separation layer of the nanofiltration membrane, thereby enhancing the assembly of the polyelectrolyte, thereby improving the retention rate for Mg 2+ The retention of magnesium sulfate by the polyelectrolyte composite hollow fiber nanofiltration membrane containing Ni-MOF / PDA (10) obtained in Example 1 is as high as 88%, the retention of magnesium sulfate by the polyelectrolyte composite hollow fiber nanofiltration membrane containing Ni-MOF / PDA (25) obtained in Example 2 is as high as 95%; and the retention of magnesium sulfate by the polyelectrolyte composite hollow fiber nanofiltration membrane containing Ni-MOF / PDA (50) obtained in Example 3 is as high as 98%.
[0132] The structural schematic diagram of Ni-MOF and Ni-MOF / PDA in the present invention is as follows Figure 1 As shown. Figure 1 It can be seen that Ni-MOF has a triangular pore structure. The double solvent method is used to modify Ni-MOF with dopamine, and the modification of Ni-MOF mixed matrix membrane can be studied and the pore size can be adjusted at the same time.
[0133] The FTIR images of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1 are as follows: Figure 2 As shown. Figure 2 It can be seen that at about 1500cm -1 The characteristic absorption peak of PDA matching the -C=C / -C=N stretching vibration can be clearly seen.
[0134] The XRD patterns of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1 are as follows: Figure 3 As shown. Figure 3 It can be seen that the XRD spectra of Ni-MOF nanocrystals and Ni-MOF / PDA nanoparticle structures are consistent with the simulated Ni-MOF crystal results, and no changes in the crystal structure were observed after PDA modification.
[0135] The adsorption / desorption diagrams of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1 are shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the N2 adsorption isotherms of the two materials are typical type i isotherms, and the specific surface areas are 1056m 2 / g and 613m 2 / g, with the decrease of adsorption capacity, the pore volume of Ni-MOF increases from 0.257 cm 3 / g decreased to 0.138 cm / g for Ni-MOF / PDA 3 / g, indicating that the polymerization inside the pores of MOF was successful.
[0136] The SEM images of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1 are as follows: Figure 5 As shown. Figure 5 It can be seen that the particle size distributions of Ni-MOF and Ni-MOF / PDA are similar, indicating that the two are similar in the size of nanoparticles.
[0137] TEM images of Ni-MOF and Ni-MOF / PDA nanoparticles in Example 1 are as follows Figure 6 As shown. Figure 6 It can be seen that no obvious PDA agglomeration phenomenon was observed during the PDA encapsulation of Ni-MOF, which indicates that the PDA encapsulation of Ni-MOF is uniform and effective, ensuring the dispersion and stability of the nanoparticles.
[0138] The contact angle diagrams of the composite hollow fiber nanofiltration membranes obtained in Comparative Example 1 and Examples 1 to 3 are as follows: Figure 7 As shown. Figure 7 It can be seen that after the polyethersulfone ultrafiltration membrane is coated with polyelectrolyte, the contact angle of the nanofiltration membrane drops from 65° of the ultrafiltration membrane to 25°. It can be seen that the polyelectrolyte coating can significantly reduce the contact angle of the membrane surface, making it easier for water molecules to wet the membrane surface, thereby improving the hydrophilicity of the nanofiltration membrane.
[0139] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite hollow fiber nanofiltration membrane, characterized in that: The steps include: 1) mixing 1,4-diphenyl(4-pyrazolyl)benzene, nickel acetate and a first solvent and drying the mixture to obtain Ni-MOF; 2) mixing Ni-MOF, dopamine hydrochloride and a second solvent and then coating with PDA to obtain Ni-MOF / PDA; 3) mixing Ni-MOF / PDA with a polycation electrolyte to obtain a polycation electrolyte containing Ni-MOF / PDA; 4) A layer-by-layer self-assembly method is used to alternately coat a polycation electrolyte solution and a polyanion electrolyte solution containing Ni-MOF / PDA on a hollow fiber ultrafiltration membrane to obtain a composite hollow fiber nanofiltration membrane.
2. The method for preparing a composite hollow fiber nanofiltration membrane according to claim 1, characterized in that: In the step 1), the first solvent is tetrahydrofuran and / or chloroform; The usage ratio of the 1,4-diphenyl(4-pyrazolyl)benzene, nickel acetate and the first solvent is 1 mol: 0.5-5 mol: 180-220 mL.
3. The method for preparing a composite hollow fiber nanofiltration membrane according to claim 2, characterized in that: In the step 1), the mixing time is 30 to 50 minutes; The drying time is 8 to 12 hours, and the drying temperature is 120 to 150°C.
4. The method for preparing a composite hollow fiber nanofiltration membrane according to claim 1 or 3, characterized in that: In the step 2), the second solvent is n-hexane; The usage ratio of the Ni-MOF, dopamine hydrochloride and the second solvent is 0.3-1 mol: 90-150 mg: 80-120 mL.
5. The method for preparing a composite hollow fiber nanofiltration membrane according to claim 4, characterized in that: In the step 2), the PDA coating step is: after mixing Ni-MOF, dopamine hydrochloride and the second solvent, removing the supernatant, adding ethanol, water and ammonia water to the obtained product and stirring, and then centrifuging to complete the PDA coating; The mixing time is 80 to 120 minutes, the dosage ratio of Ni-MOF, ethanol, water and ammonia water is 0.3 to 1 mol: 150 to 300 mL: 250 to 350 mL: 1 to 3 mL, the stirring time is 80 to 120 minutes, the centrifugal speed is 7000 to 10000 rpm, and the centrifugal time is 2 to 5 minutes.
6. The method for preparing a composite hollow fiber nanofiltration membrane according to claim 1, characterized in that: In the step 3), the polycation electrolyte is polyacrylamine hydrochloride or polystyreneamine; The molar ratio of Ni-MOF / PDA to polycation electrolyte is 5-50:50-95.
7. The method for preparing a composite hollow fiber nanofiltration membrane according to claim 5 or 6, characterized in that: In the step 3), the mixing time is 10 to 60 minutes and the mixing temperature is 15 to 25°C.
8. The method for preparing a composite hollow fiber nanofiltration membrane according to claim 1, characterized in that: In the step 4), the polyanion electrolyte is polystyrene sulfonic acid, polyacrylic acid, dextran sulfate or sodium polyvinyl sulfonate; The solvent of the polycation electrolyte solution containing Ni-MOF / PDA and the solvent of the polyanion electrolyte solution are independently sodium chloride solutions, and the concentration of the sodium chloride solution is 0.5-2.5M; the number of layers of the coating obtained by coating is 5-8 layers.
9. A composite hollow fiber nanofiltration membrane obtained by the method for preparing a composite hollow fiber nanofiltration membrane according to any one of claims 1 to 8.
10. Use of the composite hollow fiber nanofiltration membrane according to claim 9 in sewage treatment or biomedical fields.
Citation Information
Patent Citations
Antibacterial composite nanofiltration membrane and preparation method thereof
CN115155341A